Standardization of bovine lung thromboplastin according to the WHO report: Calculation of the ISI value and the prothrombin time as INR - (:unkn) unknown (My University, 2004)
Thromboplastin is an important reagent for prothrombin time (PT) test. Various types of thromboplastin are prepared commercially and it is essential that each reagent is correctly standardized, in order to be able to interpret the results of the prothrombin time test. This will ensure that the results of tests with different products and batches are reproducible and can be compared. For this reason we prepared thromboplastin extract from bovine lung and calibrated according to the thirty-third report of the WHO Expert Committee on Biological Standardization. With this procedure, standardization parameter called International Sensitivity Index (ISI) was calculated and it is used for converting the PT values from seconds to International Normalized Ratio (INE). By this calculation it is possible to compare the PT results, which were performed by different thromboplastins. After standardization we used this thromboplastin extract for PT test and compared this extract with the commercial kit for PT test. In conclusion the results of our evaluation show that our thromboplastin extract can be used safely as a reagent for PT tests instead of commercial PT kit.
Keywords: Bovine lung; INR; ISI; Prothrombin time; Thromboplastin